Feigned resignation as political strategy: cracking the mysterious case of Phibunsongkhram's reversal of resignation in 1943. (3rd July 2021) - Charoenvattananukul, Peera
ABSTRACT: On 12 February 1943, Field Marshal Phibunsongkhram (Phibun), Thailand's prime minister, handed a formal letter of resignation to the Council of Regency. The news of the prime minister's sudden departure shocked the two regents and other cabinet ministers. Nevertheless, when public radio broadcasters announced the news of the premier's resignation, Phibun retracted the resignation decision and sought to avenge those who drove him from office. Why did he resign and then reverse the decision? How can such confusing and irrational behaviours be explained when they remain a mystery even to historians? This article claims that Phibun engaged in a 'feigned resignation strategy', whereby he pretended to resign to see the reactions of different political factions and to test political loyalty. This article traces his pattern of feigned resignations from 1939 to 1944 to prove how he mastered such a strategy. Archival records indicate that he frequently informed his associates that he wished to resign from office but then eventually reversed his decision. Drawing from the concept of feigned resignation strategy, this article argues that the resignation in February 1943 stemmed from Phibun's motive to identify and root out political opponents.